The Role of Green HRM in Mediating the Influence of Leadership on Employee Performance at Hotel in Kuta - Mastra, Agus Satyananda; Santoso, R Tri Priyono Budi; Utama, I Gusti Bagus Rai; Nainggolan, Gilbert (Eastasouth Institute, 2025)
This study aims to determine the influence of leadership on employee performance as mediated by Green HRM. Green HRM is an approach to human resource management that integrates environmentally friendly practices to support organizational sustainability and reduce negative environmental impacts. This study utilizes Social Exchange Theory (SET) and Self-Determination Theory (SDT) to provide a perspective on how the relationship between a company and its employees influences their performance outcomes. This quantitative study employed a survey method with questionnaires and closed-ended triangulation interviews. The study was conducted in five star-rated hotels that have implemented Green HRM, with a sample of 91 registered employees. Data analysis used path analysis.